Uncovering Status and Legality of Digital Rupiah as Legal Tender: Using Dignified Justice Theory - Kameo Jeferson; Prasetyo Teguh; Janpieter Hutajulu Marihot; Rawni Arndarnijariah Faqi; Nur Chika Amitha Exsa (SHS Web of Conferences, 2024)
Modern digital and telecommunication technologies have been and will continue to be factors in the emergence of innovative products such as the Central Bank Digital Currency (CBDC) called Rupiah Digital. However, the plan to issue Digital Rupiah is not without problems. Primarily, the problem is related to the clarity of the legal status of Digital Rupiah as a legal tender. Using normative legal research methods, this study finds that Article 23B of the 1945 Constitution of the Republic of Indonesia has not explicitly regulated digital currencies. There is a rechtsvacuum of the legal tender status of Digital Rupiah at the constitutional level. Besides legally, no regulations regarding status of legal tender of Digital Rupiah in its equality with Paper (bank notes) and Metal Rupiah. However, this research has found a new Act supporting the status and legality of legal tender of Digital Rupiah. The legal theory that navigated the findings of CBDC’s legal regulatory framework is the Dignified Justice theory. Under the Dignified Justice theory, despite the inevitable need for comparative law, Pancasila must still be the source of all legal sources for the existence of the Digital Rupiah.